2021
DOI: 10.3390/polym13030427
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylidene Fluoride Membrane Via Vapour Induced Phase Separation for Oil/Water Emulsion Filtration

Abstract: Membrane-based technology is an attractive option for the treatment of oily wastewater because of its high oil removal efficiency, small footprint and operational simplicity. However, filtration performance is highly restricted by membrane fouling, especially when treating oil/water emulsion as a result of strong interaction between oil droplets and the hydrophobic property of the membrane. This study explores the fabrication of polyvinylidene fluoride (PVDF)-based membrane via the vapour induced phase separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…As expected, the total fouling for all three types of membranes showed an increasing trend with the increasing filtration cycles. The trend of multiple cycle performance is consistent with our earlier report treating the same feed following similar filtration cycles [10][11][12]47]. The three membranes pose quite distinct fouling reversibility.…”
Section: Membrane Fouling Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…As expected, the total fouling for all three types of membranes showed an increasing trend with the increasing filtration cycles. The trend of multiple cycle performance is consistent with our earlier report treating the same feed following similar filtration cycles [10][11][12]47]. The three membranes pose quite distinct fouling reversibility.…”
Section: Membrane Fouling Analysissupporting
confidence: 89%
“…Conventional methods (flotation and coagulation) for the treatment of stable oil/water emulsions are less effective in handling micron-sized emulsion droplets and finely dispersed oil particles [9]. The membrane-based process is seen as one of the emerging methods for treating oil/water emulsion wastewater that has been shown effective in handling low concentration of oil (<1000 ppm) in water [10][11][12]. It outstands the conventional separation techniques for simplicity, continuous, faster, and cost-effectiveness due to their low energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Oil droplets in oil/water emulsion easily foul plain PVDF membrane since oil droplets can strongly adhere to the membrane surface [10]. Fortunately, PVDF-based membrane can be made hydrophilic by incorporating additives during membrane fabrication to overcome its high membrane fouling propensity [11,12]. For instance, Cui et al [4] reported a biomimetic surface modification by virtue of the polydopamine anchored by silicone dioxide on the PVDF membrane by enzymatic oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Slight increments of the water fluxes were observed in all cases but were statistically insignificant. Judging from the high stability of PVDF, a small change in flux can be attributed to the degradation of residual TA that left the void and turned the membrane structure to be more porous and/or the membrane pore to be larger, as also occurred when employing a dragon blood in resin [ 6 ], PEG [ 38 ] or PVP as additive [ 39 ]. However, the water flux increment for the pristine PVDF membranes suggests that the treatment might also affect the PVDF polymer.…”
Section: Resultsmentioning
confidence: 99%